Immediate Effect on Ground Reaction Forces Induced by Step Training Based on Discrete Skill during Gait in Poststroke Individuals: A Pilot Study. (19th May 2020) - Wakida, Masanori; Ohata, Koji; Hashiguchi, Yu; Mori, Kimihiko; Hase, Kimitaka; Yamada, Shigehito
Abstract : Background/Aim . Improving walking ability, especially the step-to-step transition control, is important in individuals after stroke. Although walking is a continuous skill, the discrete skills of gait, defined as movements with a clear beginning and end, may effectively modify walking performance. This pilot study shows the immediate effects of a discrete skill-based step training on ground reaction forces (GRFs) during gait in individuals with chronic hemiplegia following stroke. Methods . Twenty-two community-dwelling patients with chronic hemiplegia participated in this study. Eight participants performed only discrete-skill step training during the loading response phase, focusing on paretic hip extension movement (LR group). Another eight performed only discrete-skill step training during the preswing phase, focusing on paretic swing movement (PSw group). The remaining six were trained using both training methods, with at least 6 months in each group to washout the influence of previous training. Therefore, the final number of participants in each group was 14. The braking and propulsive forces of GRFs were measured during gait before and after 30 repetitions of the discrete-skill step training. Results . Although both groups showed a significant increase in stride length, walking speed was increased only in the LR group. The PSw group showed an increase in braking forces of both sides without any change in propulsion. In the LR group, paretic braking impulse did not change, while nonparetic propulsion increased. Conclusion . The discrete-skill step training during loading response phase induced an increase in nonparetic propulsion, resulting in increased walking speed. This study provides a clear understanding of immediate effects of the discrete-skill step training in patients with chronic stroke and helps improve interventions in long-term rehabilitation.